THE USE OF EUPHEMISM IN DONALD TRUMP AMERICAN ARABIC SUMMIT SPEECH - Anita Firdausi Nuzula (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2020)
Euphemism is a language phenomenon that exists in society. As social beings, human uses a language to communicate each other. This is for delivering a message or information from one to another without miss the idea, opinion, or feeling. The speaker can use the euphemistic expression during delivering the message to reach a certain goal. Thus, it can be found in the middle of conversation, include in the special speech which has been delivered by a representative of nation (president). This study aimed to explain the types, forms and functions of euphemism that are found in a speech of Donald Trump in American-Arabic summit. This study is descriptive qualitative based on phenomena of euphemism in spoken language. The writer used the theory of Rawson to analyze the type and form of euphemism expression, and the theory of Sebkova to analyze the function of the use euphemism expression. The result of this study shows that there are four type of euphemism found in the speech of Donald Trump in the American Arabic summit (circumlocution, widening, metaphor, and abbreviation). There are six functions of euphemism are found in the speech of Donald Trump in the American Arabic summit. Euphemism may be used substitute bad connotation of utterance; euphemism may be used to protect someone or group of people of feeling shame; euphemism may be used as alternative for taboo word; euphemism may be used to neutralizing the unpleasant word; euphemism may be used to protect personal name or group; euphemism may be used to explain or exaggerate. The function of euphemism that is mostly used is explain in exaggerate way and avoid the word of taboo.Keywords: Euphemism, Political Speech, Donald Trump Speech.